Logistics Engineering and Management - Lynch, Shelley (USA Willford Press, 2019)
The field of engineering that is concerned with the organization of the purchase, storage, warehousing, transport and distribution of goods and materials is known as logistics engineering. It also encompasses the aspects of repair capability, training, demand history, spares inventory, etc. The supply chain management is an important aspect of logistics engineering. It is concerned with the procurement of raw materials as well as the distribution of the products to the end customer. Some of the areas of focus in logistics engineering are purchasing, sourcing, inventory control, customer service, warehousing, etc. This book is compiled in such a manner, that it will provide in-depth knowledge about the theory and practice of logistics engineering and management. Most of the topics introduced herein cover new techniques and the applications of this field. Those in search of information to further their knowledge will be greatly assisted by this textbook.
Keywords: Management; Industrial Engineering; Business logistics--Management